Laser Raman evidence for new cloverleaf secondary structures for eukaryotic 5.8S RNA and prokaryotic 5S RNA. - Luoma, G A (1978)
Neither of the two previously proposed secondary structures for eukaryotic 5.8S RNA is consistent with the present laser Raman results. A new, highly stable "cloverleaf" secondary structure not only fits the Raman data but also accounts for previously determined enzymatic partial cleavage patterns, base sequence and pairing homologies, and G-C and A-U base pair numbers and ratios. The new cloverleaf model also conserves several structural features (constant loops, bulges, and stems) consistent with known 5.8S RNA functions. Finally, we propose a similar new cloverleaf secondary structure for Escherichia coli 5S RNA, consonant with many known properties of prokaryotic 5S RNA.